2020
DOI: 10.5194/nhess-20-3215-2020
|View full text |Cite
|
Sign up to set email alerts
|

Detecting precursors of an imminent landslide along the Jinsha River

Abstract: Abstract. Landslides are major hazards that may pose serious threats to mountain communities. Even landslides in remote mountains could have non-negligible impacts on populous regions by blocking large rivers and forming dam-breached mega floods. Usually, there are slope deformations before major landslides occur, and detecting precursors such as slope movement before major landslides is important for preventing possible disasters. In this work, we applied multi-temporal optical remote sensing images (Landsat … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…There are 13 bands with a spatial resolution of 10, 20, and 60 m. Nearinfrared (NIR), red, green, and blue are four bands with 10 m in spatial resolution. The 10-m red band is the most frequently used data to detect surface deformation (Yang et al, 2020a;Qi et al, 2021).…”
Section: Deformation Derived By Pixel Offset Tracking and Time-series...mentioning
confidence: 99%
See 1 more Smart Citation
“…There are 13 bands with a spatial resolution of 10, 20, and 60 m. Nearinfrared (NIR), red, green, and blue are four bands with 10 m in spatial resolution. The 10-m red band is the most frequently used data to detect surface deformation (Yang et al, 2020a;Qi et al, 2021).…”
Section: Deformation Derived By Pixel Offset Tracking and Time-series...mentioning
confidence: 99%
“…For this work, we selected images that were least affected by clouds. We used the COSI-Corr software, which was developed by a team in the California Institute of Technology (Leprince et al, 2007) and is a frequently used sub-pixel offset tracking method to derive surface deformation in Sentinel-2 images (Bontemps et al, 2018;Lacroix et al, 2018;Yang et al, 2020a;Qi et al, 2021). To derive surface deformation with the software, we must compose a pair of two images acquired at different dates.…”
Section: Deformation Derived By Pixel Offset Tracking and Time-series...mentioning
confidence: 99%
“…The landslide area is crossed by the N-NW-trending Jinsha tectonic belt, forming complex structural conditions with multiple faults and structural blocks and undermining the slope with long-term tectonic activities [124]. It is widely accepted that this landslide event occurred as a result of long-term slope deformation [74,124,[126][127][128][129][130][131]. Liu et al [132] collected 28 Advanced Land Observing Satellite (ALOS) SAR images from January 2007 to August 2018 to characterize the deformation history and temporal evolution of the Baige landslide and used a new offset tracking method to correct the SAR image deformation errors; they found that the maximum cumulative deformation of the Baige landslide in the radar line of sight reached approximately −60 m. Li et al [71] used ALOS and Sentinel-1 spaceborne SAR data from 2007 to 2018 to study the temporal evolution of the surface displacement of the Baige landslide before the first collapse.…”
Section: The Baige Landslidementioning
confidence: 99%
“…The Landsat-8 satellite payload consists of two instruments: Operational Land Imager (OLI) and Thermal Infrared Sensor (TIRS). The OLI provides nine bands at a spatial resolution of 30 m. TIRS provides two separate thermal infrared bands at a resolution of 100 m. Landsat series data are currently widely used in many research fields, such as natural resource protection [ 34 ], energy exploration [ 35 ], environmental management [ 36 ], and natural disaster monitoring [ 37 ].…”
Section: Study Area and Data Sourcesmentioning
confidence: 99%